Book Review S. Røed-Larsen, J. Stoop and E. Funnemark Shaping Public Safety Investigations of Accidents in Europe - Elvik, Rune (European Journal of Transport and Infrastructure Research, 2006)
Shaping public safety investigations of accidents in Europe is a book edited by Sverre Røed Larsen, John Stoop and Espen Funnemark. The book is a report from the European Safety, Reliability and Data Association (ESreDA), published in 2005 by Det norske Veritas (ISBN 82 5150304 3). The book consists of two parts. The first part of the book, written by the three editors, provides an overview of the current state-of-the-art of public safety investigations of major accidents in Europe. The second part of the book consists of eight papers by different authors, dealing with different topics related to in-depth investigation of accidents. The book explicitly lists the audience it is intended for – a rare feature in scientific books. The primary target groups for the book include national governmental bodies responsible for safety, accident investigation boards, consultants in the field and researchers. The objective of the book is not merely to describe the current state-of-the-art of safety investigations of accidents in Europe, but to influence such investigations; hence the title shaping public safety investigations. The book notes that major changes in the approach taken to in-depth investigation of accidents have taken place in recent years in Europe. Traditionally, these investigations were intended merely to identify the immediate causes of an accident. Today, accident investigations increasingly also aim for the prevention of accidents. This means that modern accident investigations adopt a much broader perspective on contributing factors than past investigations did, looking, for example, for elements of organisational culture and safety management that may contribute to accidents. Moreover, the organisation of safety investigations is changing. In the past, ad hoc commissions were created to investigate each accident, and dissolved once the task was accomplished. Today, accident investigation boards are often permanent institutions that cover a broader range of tasks, sometimes including the monitoring of safety by investigating unwanted events that do not end up as major accidents.